An outbreak of Cryptosporidium parvum linked to pasteurised milk from a vending machine in England: a descriptive study, March 2021. (28th October 2022) - Gopfert, Anya; Chalmers, Rachel M.; Whittingham, Sarah; Wilson, Laura; van Hove, Maria; Ferraro, Claire F.; Robinson, Guy; Young, Nick; Nozad, Bayad
Abstract: We describe the investigations and management of a Cryptosporidium parvum outbreak of linked to consumption of pasteurised milk from a vending machine. Multiple locus variable number of tandem repeats analysis was newly used, confirming that C. parvum detected in human cases was indistinguishable from that in a calf on the farm. This strengthened the evidence for milk from an on-farm vending machine as the source of the outbreak because of post-pasteurisation contamination. Bacteriological indicators of post-pasteurisation contamination persisted after the initial hygiene improvement notice. We propose that on-farm milk vending machines may represent an emerging public health risk.